Adherence and persistence with branded antidepressants and generic SSRIs among managed care patients with major depressive disorder - Xianchen Liu; Yi Chen; Douglas E Faries; et al (Dove Medical Press, 2011)
Xianchen Liu1,2, Yi Chen3, Douglas E Faries31Former employee, Eli Lilly and Company, Indianapolis, Indiana, USA; 2Indiana University Department of Psychiatry, Indianapolis, Indiana, USA; 3Eli Lilly and Company, Indianapolis, Indiana, USAObjective: This study compared adherence and persistence of three branded antidepressants: the serotonin and norepinephrine reuptake inhibitors (SNRIs) duloxetine and venlafaxine XR, and the selective serotonin reuptake inhibitor (SSRI) escitalopram; and generic selective SSRIs, and examined demographic and clinical predictors of adherence and persistence in patients with major depressive disorder in usual care settings.Method: A total of 44,026 patients (18 to 64 years) from a large commercial administrative claims database were classified as initiators of duloxetine (n = 7,567), venlafaxine XR (n = 6,106), escitalopram (n = 10,239), or generic SSRIs (n = 20,114) during 2006. Adherence was defined as the medication possession ratio of ≥ 0.8 and persistence as the length of therapy without exceeding a 15-day gap. Pairwise comparisons from multivariate logistic regression and Cox proportional hazards models were performed to examine predictors of adherence and persistence.Results: Adherence rate after one year was significantly higher in duloxetine recipients (38.1%) than patients treated with venlafaxine XR (34.0%), escitalopram (25.4%), or generic SSRIs (25.5%) (all P < 0.01). Duloxetine recipients stayed on medication longer (158.5 days) than those receiving venlafaxine XR (149.6 days), escitalopram (129.1 days), or generic SSRIs (130.2 days) (all P < 0.001). Compared with patients treated with escitalopram or generic SSRIs, venlafaxine XR recipients had better adherence and longer persistence (P < 0.001). In addition, being aged 36 years or more, hypersomnia, anxiety disorders, and prior use of antidepressants were associated with increased adherence and persistence, while the opposite was true for comorbid chronic pain conditions, alcohol and drug dependence, and prior use of amphetamine.Conclusion: Compared with SSRIs, the SNRIs appear to have better adherence and persistence. Among SNRIs, duloxetine had statistically significantly better adherence and persistence than venlafaxine XR, though differences were relatively small and further research is needed to assess whether these translate into clinically and economically meaningful outcomes. Adherence and persistence with antidepressant therapy were associated with age, multiple comorbid conditions, and prior use of medications.Keywords: treatment adherence, length of therapy, antidepressants, major depression, retrospective analysis